2006
DOI: 10.1002/tea.20100
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of intertextuality in concept construction: Urban second graders make sense of evaporation, boiling, and condensation

Abstract: The study explores urban second graders' thinking and talking about the concepts of evaporation, boiling, and condensation that emerged in the context of intertextuality within an integrated science‐literacy unit on the topic of States of Matter, which emphasized the water cycle. In that unit, children and teacher engaged in a variety of activities (reading information books, doing hands‐on explorations, writing, drawing, discussing) in a dialogically oriented way where teacher and children shared the power an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 49 publications
1
57
0
1
Order By: Relevance
“…It is important to understand how purposefully prepared engineering literature presented in the format of picture book children's stories impacts learning in emergent readers. The influence of literature on children's thinking about engineering and the connection children make between science and engineering can be observed through illustrative data and feedback after exposure to engineering literature [4][5][6][7][8].…”
Section: Early Engineering Literacymentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to understand how purposefully prepared engineering literature presented in the format of picture book children's stories impacts learning in emergent readers. The influence of literature on children's thinking about engineering and the connection children make between science and engineering can be observed through illustrative data and feedback after exposure to engineering literature [4][5][6][7][8].…”
Section: Early Engineering Literacymentioning
confidence: 99%
“…Text reads "A firework becoming a rainbow". The children's drawings show the advanced ways that they think about ideas [5,7]. When asked to draw what they would design when they were an engineer, the students did not hesitate to immediately picture themselves in this role.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations
“…However, the previous studies showed that students at various ages have alternative frameworks on the concept of condensation (Kruger & Summers, 1989;Bar & Travis, 1991;Lee et al, 1993;Chang, 1999;Gopal et al, 2004) covering various topics such as vapor pressure (Gopal et al 2004), condensation in opened system (Paik et al, 2004), condensation in closed system (Costu, 2006), the concept and the phases of matter (Johnson, 2005) and the development of the students conceptualization in understanding the change of phases (Varelas et al, 2006). For example, a study by Costu et al (2012) found that first year students in the department of primary science education listed eight difficulties and alternative frameworks namely water vapor cannot be converted to water, water vapor cannot exist in the air at all times, hydrogen and oxygen, the components of water vapor exist in the air other than the water vapor itself, the molecules of water vapor are lighter than the molecules of water, the air is condensed as water, the condensation occurs because the vapor pressure is rising and only water vapor exists in the air during winter and ice on the cold surface will melt and form water droplets (condensation in the opened system).…”
Section: Introductionmentioning
confidence: 99%